Implant-free loop tenodesis compared to arthroscopic anchor tenodesis for the treatment of long head of biceps tendon disorders (LOOPTEN trial): study protocol for a multi-center non-inferiority randomized controlled trial - Leopold Henssler; Florian Zeman; Doruk Akgün; Kathi Thiele; Stephan Pauly; Stefan Greiner; Andreas Voss; Christian Gerhardt; Lars-Johannes Lehmann; Gunnar Huppertz; Magdalena Elsner; Volker Alt; et al. (BMC Musculoskeletal Disorders)
Abstract Background Pathologies of the long head of the biceps (LHB) tendon are frequently seen as concomitant pathologies during arthroscopic surgery for rotator cuff injuries or the labroligamentous complex of the shoulder. Currently, there are two treatment options: Tenotomy is quick and easy to perform with low complications rates, but has limited functional results, especially in demanding patients; tenodesis of the tendon has shown beneficial cosmetic and functional results, but usually requires an implant for tendon-to-bone attachment and, therefore, carries the risk of implant-related complications. The implant-free loop tenodesis (LT) procedure was developed to combine the advantages of both treatment modalities and has shown promising functional and cosmetic results in a prospective pilot study. This study aims to establish the implant-free LT procedure versus arthroscopic anchor tenodesis (AAT) for the treatment of LHB pathologies during shoulder arthroscopy in terms of structural and functional outcome. Methods A national multi-center, two-arm, parallel-group, randomized, controlled, non-inferiority trial will be conducted. Patients are eligible for trial participation if they are at least 18 years of age and present to one of the five enrolling centers with LHB tendon-associated complaints and MRI-confirmed LHB tendinopathy, instability due to SLAP or pulley lesions, or partial rupture. Patients with current or previous shoulder injury that would interfere with post-treatment rehabilitation or study assessment will be excluded from study participation. Participating patients will be randomized 1:1 to receive either LT or AAT and will be followed up for 24 months after surgery. The primary endpoint will be the functional and cosmetic outcome as assessed by the biceps-specific LHB score at 12 months after surgery. Secondary outcomes include assessment of surgery-related complications, overall shoulder and arm function, and structural outcome as evaluated by ultrasound and an additional MRI scan at the final study visit. Discussion The study will evaluate whether the implant-free loop tenodesis procedure is non-inferior to arthroscopic implant-based tenodesis in terms of functional and cosmetic results at 12 months post-treatment. Trial registration Trial was prospectively registered at the German Clinical Trials Register (DRKS) on 12th June 2024, Registration-ID DRKS00034361, https://drks.de/search/de/trial/DRKS00034361 .